Local limit theorem and asymptotic expansion for the Sums of independent lattice random variables - Mitalauskas, A.; Statulevičius, V. (Lithuanian Mathematical Journal, 1966)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. А. Миталаускас, В. А. Статулявичюс. Локальные предельные теоремы и асимптотические разложения для сумм независимых решетчатых случайных величин A. Mitalauskas, V. Statulevičius. Lokalinė ribinė teorema ir asimptotinis išdėstymas nepriklausomų rėtinių atsitiktinių dydžių sumom